Motivasi Inovasi Kewirausahaan Lembaga Dakwah di Era Disruptif - Kuswanto, Haryono Hadi; Castrawijaya, Cecep (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
Entrepreneurial innovation motivation is the urge to make changes that occur within a company or missionary institution in order to adapt to the environment or market demand. For da'wah institutions, the main challenge in this disruptive era is how to maintain operational continuity while meeting the growing needs of the congregation. One solution that can be implemented is by integrating technological innovation and developing entrepreneurial products that can support da'wah financially. This research uses a qualitative descriptive analysis approach, with a library research method (Library Research). Da'wah institutions need to create products or services that are not only oriented towards financial profits, but also provide social benefits, including supporting missionary activities.